UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA MELALUI MODEL PROBLEM BASED LEARNING DI KELAS XI SMA METHODIST 2 PALEMBANG - Amirotul Qudsiy; Lusiana Lusiana; Tina Mora Silalahi (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2023)
This study aims to improve the learning outcomes of mathematics subject of class XI SMA Methodist 2 Palembang. This research incorporates Classroom Action Research on class XI 4 SMA Methodist 2 Palembang as the subject. The data was collected through observation, documentation, and tests and analyzed using a descriptive quantitative approach. This research found: (1) The student's cognitive learning outcomes in the first cycle were 65% in the first meeting and 71% in the second. Then, in cycle II, it increased to 81% in the first meeting and 88% in the second. (2) The student's affective learning outcomes in cycle I acquired an average of 86.32 in the first meeting and 88.89 in the second. Then, in cycle II, it increased with an average of 91.45 in the first meeting and 93.59 in the second, which was in the "Very Good" category. (3) The student's psychomotor learning outcomes in cycle I acquired an average of 80.45 in the first meeting and 83.04 in the second. Then, in cycle II, it increased with an average of 85.26 in the first meeting and 88.14 in the second, which was in the "Good" category. The problem-based learning model can be concluded to improve the mathematics learning results of class XI 4 SMA Methodist 2 Palembang